Aim High: Pressing for a Radical and Global Approach to Sustainable Design. (3rd January 2018) - Robertson, Craig
Abstract : The importance of major progress in designing for sustainability and resilience is indisputable, and the arguments put forward throughout this issue of 3 are highly commendable. But – asksCraig Robertson, Head of Sustainability at London architecture firm Allford Hall Monaghan Morris (AHMM) – do they go far enough? Are we still too focused on our own backyards rather than the needs of our fellow human beings worldwide? Have we yet grasped the level of adaptability that is required not only to protect us in the present, but to future‐proof the built environment for generations to come? And what must governments, professional bodies and indeed individuals do to bring about the total paradigm shift that is so urgently needed?